Research on Network Database Laboratory Instrument Management Information System Based on Content Query - Yang, Bo (IOP conference series. Materials Science and Engineering, 2020)
With the requirement of further opening of laboratories, it is increasingly important to carry out open management of laboratories on the basis of traditional laboratory management. In this paper, Windows operating system is used as the operating platform, ASP technology and databases such as Microsoft Access 2013 and Microsoft SQL Serv-er 2000 are used as development tools. This paper mainly discusses how to build an object-oriented image database based on content query based on the existing database management system, proposes a hierarchical model of the system, and presents a data structure model of the image database. A laboratory instrument management information system with B / S mode based on content query network database is developed. In the specific teaching, the laboratory should be fully open in the experiment content, experiment equipment, experiment time and experiment management, so as to make the laboratory open management scientific and improve the utilization rate of instruments and equipment.